Analisis Waste Pemotongan Material Plate Menggunakan Metode Value Stream Mapping (VSM) dan Root Cause Analysis (RCA) di PT. YYY - Nando, Fiky Two; Pamungkas, Ferio Aji; Ardiansyah, M. Dava; Febriyanti, Amalia Rizka; Subrakah, Bagas; Mawadati, Argaditia (Indonesian Journal of Engineering and Technological Innovation, 2025)
This research was conducted at PT. YYY, a manufacturing company engaged in fabrication with a focus on the plate cutting process, which plays an important role in determining the accuracy, precision, and quality of production results. However, various problems were still found such as cutting defects, inappropriate dimensions, and deformation due to heat that caused rework and wasted time and costs. To overcome this, this study applied the Root Cause Analysis (RCA) and Value Stream Mapping (VSM) methods to identify the root causes of defects and non-value added activities (Non-Value Added). The results of the analysis showed a total of Non-Value Added (NVA) of 80 minutes and a waiting time of 130 minutes, with the main causes coming from the Man, Method, Machine, Environment, and System aspects. Through the implementation of improvements such as work standardization, measuring instrument calibration, area layout arrangement, and digitalization of the material monitoring system, increased efficiency, reduced waste, and improved overall production quality and timeliness were achieved.